A conceptual model of disasters encompassing multiple stakeholder domains. (18th August 2008) - Kruchten, Philippe; Woo, Carson; Monu, Kafui; Sotoodeh, Mandana
Understanding the interdependencies of critical infrastructures (power, transport, communication, etc.) is essential in emergency preparedness and response in the face of disasters. Unfortunately, many factors (e.g., the unwillingness to disclose or share critical data) prohibited the complete development of such an understanding. As an alternative solution, this paper presents a conceptual model – an ontology – of disasters affecting critical infrastructures. We bring humans into the loop and distinguish between the physical and social interdependencies between infrastructures, where the social layer deals with communication and coordination among the representatives (either humans or intelligent agents) of the various critical infrastructures. We validated our conceptual model with the people responsible for disaster management from several different critical infrastructures and through a case study. We also derived tools from the model to provide decision support. We expect that this conceptual model can later be used by people as a common language to communicate, analyse and simulate their interdependencies without having to disclose all critical and confidential data.